Récits d’absence : l’intimité familiale au prisme de la séparation - Constance De Gourcy (Sociologies)
The aim of this article is to understand the complex relationship between attachment and intimacy within families undergoing a family reunification procedure from France to North Africa. The administrative temporality of the procedure produces a time that stretches because of the steps to be taken to obtain a visa and put an end to the separation. Faced with this temporality, how can the link be maintained at a distance and the common ground extended? Using stories of absence, we’ll look at how to capture an intimacy that seeks to preserve the memory of what once was, while at the same time being subject to the need to adjust to distant life courses, with all the ambivalence that distance entails.